PENGARUH ISLAMIC CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP REPUTASI DAN KINERJA KEUANGAN PERUSAHAAN - Fauzizah Nasyirotun Nisa; Dian Kurniasari (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
The purpose of this research are to analyze the practice of social responsibility disclosure on companies listed in the Jakarta Islamic Index (JII) and to test the effect of disclosure of corporate social responsibility toprofitability ROA (ratio of return on assets) and ROE (ratio of return on equity) as well as the company's reputation measured from the stock price. This research are conducted using a sample of 39 go public companies that has been registered at the Jakarta Islamic Index (JII) using annual reports from 2012 to 2014. Methods of sample selection using purposive sampling. The analysis model is a simple regression. The results showed that the level of social responsibility disclosure of significant effect on ROA on firm, level of social responsibility disclosure a significant effect on ROE and the company's reputation.